THE CORRELATION BETWEEN LEARNING HABIT AND ENGLISH ACHIEVEMENT OF SECOND YEAR STUDENT AT ISLAMIC SENIOR HIGH SCHOOL 2 PONOROGO - Sunarti, Sunarti; Sujito, Sujito (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Learning habit are behaviours that children engage in throughout learning activities, both at school and at home. learning habit carried out by students are different. In other words, learning habit are ways of learning that done by students to acquire knowledge. The formation of good learning habit can be seen from the methods of students in learning and the alertness of students in learning. Student learning activities at school such as the way students follow lessons in class and concentrate while studying as well as learning activities outside the classroom such as reading textbooks and doing assignments. Thus, learning habit play a crucial role in the development of good learning achievement. The goal of this research was to determine if learning habit and English achievement of second-year students at Islamic senior high school 2 Ponorogo were significantly correlated. The research employed a correlation design and quantitative methodology. There were 214 second-year natural science students from Islamic senior high school 2 Ponorogo as a population. To choose the sample, the researcher employed the purposive sampling approach. Therefore, there were 62 students in the sample as a whole in this research. The researcher measured students’ learning habit using questionnaires, and students’ English achievement was measured using documentation from the score of odd semester report cards. The data was analyzed using person-product moment correlation and descriptive statistics. The findings show a positive correlation between learning habit and English achievement of second year natural science students at Islamic senior high school 2 Ponorogo. Thus, it is possible to assume that the students’ learning achievement increases with their improved learning habit.